Tailoring rice varieties to consumer preferences induced by cultural and colonial heritage: Lessons from New Rice for Africa (NERICA) in The Gambia - Britwum, Kofi; Demont, Matty (SAGE Publications, 2021)
Rice breeding priorities in Africa often focus on agronomic gains. However, being a net importer of rice, the continent’s varietal replacement success also crucially hinges on new varieties’ market competitiveness vis-à-vis imports. Markets have been profoundly shaped by cultural and colonial heritage. Indigenous preferences for African rice can be traced back to ancient rice domestication and have been subsequently influenced by Asian rice import standards as a result of colonial import substitution policies. New Rice for Africa (NERICA) crosses between African and Asian rice species have the potential to reconcile these dual indigenous/import preferences, but little is known about their market competitiveness. We use auction market data to assess the intrinsic and extrinsic consumer value of NERICA in The Gambia relative to two market standards: branded, Asian rice imports and the most popular locally grown Asian rice variety. We categorize rice consumers into four market segments, based on their heritage as evidenced by their preferences and genealogical lineages. NERICA outperforms both Asian rice standards in terms of market competitiveness, and its value is further reinforced by colonial heritage and labeling, but somewhat weakened by cultural heritage. Consumers were found to pay price premiums for NERICA in the range of 5% to 22% relative to Asian rice imports, with the highest premiums offered by consumers with colonial heritage, representing 86% of the sample. Maintaining and expanding this market will require breeders to incorporate trait mixes that reconcile agronomic gains and consumer preferences induced by cultural and colonial heritage.